Modelling storm-induced beach morphological change in a meso-tidal, reflective beach using XBeach - Vousdoukas, M. I. (2018)
Extensive XBeach testing took place against field topographic and bathymetric measurements of storm morphological impact at the mesotidal, reflective Faro Beach (S. Portugal). Five monitored events have been selected for XBeach calibration and sets of runs for 768 different set-ups, showed that alongshore profile morphology variations even for the same site, may require different calibration settings, in order to achieve optimal performance. XBeach performed better with higher facua and wetslope values at the reflective parts of the study area and with lower values at the less steep ones. Model sensitivity to calibration settings appeared to increase with beach slope; while the majority of the tested set-ups resulted in negative Brier Skill Scores (BSS). The main discrepancies compared to the field measurements were related to the overestimation of berm erosion and the intense avalanching/beach scarp formation; which rarely occur at the study site. Moreover, the simulations resulted in morphological change within a narrower profile section than observed; and did not accurately simulate offshore bar formation. The study highlights that predicting beach profile morphodynamic response during storm events at steep reflective beaches with XBeach may be more difficult than at intermediate beaches. However, the results can be satisfactory after proper calibration and for the present study the optimal cases resulted in BSS of the range 0.2-0.7. The best performance was obtained by deactivating long wave stirring, wave-current interaction and equilibrium sediment computation (lws=0, wci=0, turb=0, respectively); keeping directional spreading of long waves and groundwater flow on (nspr=1, gwf=1, respectively); and using the lower morfac, facua and wetslope parameters (at the present case morfac=5, facua=0.1 and wetslope=0.2).